Comprehensive targeted treatment options available for Breast cancer stem cells; A literature review of the last 10 years’ developments - Lubna Mushtaque Vohra; Mehwish Mooghal; Wajiha Khan; Hassan Sohail; Sana Zeeshan5 (Journal of the Pakistan Medical Association, 2023)
Breast Cancer Stem Cells (BCSCs), unlike normal breast cells, exhibit the potential for self-regeneration and tumour formation and express unique markers. Studies have highlighted their role in tumour progression, recurrence, and treatment resistance. BCSCs can be one of the reasons that resistance is encountered despite recent advances in the treatment of breast cancer (BC). This review underlines the clinical implications at the molecular level of different cellular pathways, cellular level interactions in Tumour Micro Environment (TME), and types of markers and receptors involved in tumorigenesis. It accentuates the importance of comprehensive targeted treatment options available for BCSCs so that targeted modalities can be introduced to deal with treatment resistance. Stem cells (SCs) are a developing field, and limited data is available from our country to use stem cell-targeted treatment plans as a therapeutic option. Therefore, this literature review will provide insight for future research in this domain. Continued...